Diabetes Policies and Pharmacy- -based Diabetes Interventions in Portugal: A Comprehensive Review - S Costa; MR Horta; R Santos; Z Mendes; I Jacinto; J Guerreiro; M Cary; A Miranda; Helling; AP Martins (Formifarma, LDA., 2019)
Background Pharmacy-based interventions are complex public health endeavors which include, but are not restricted to, the conventional medication supply role. In diabetes, such interventions may improve patients' outcomes. The aim of this study was to review relevant policies and research developed in Portugal directed at pharmacy-based diabetes interventions, and to inform future policies, practice and research in collaborative practice with primary care. Research method An exploratory review of diabetes legislation and policy papers, as well as a comprehensive review in Embase, MEDLINE (via Ovid and PubMed), Google Scholar, and grey literature until November 2017 was performed. Results Sixteen policy papers and 10 studies were included in the analysis. Positive evidence from pharmacy interventions was retrieved concerning screening individuals at risk, screening uncontrolled patients, managing diabetes, and supporting self-monitoring. Conclusions Some consistency in favorable findings, but also room for improvements in health policies, intervention design and research methods, were observed. Published in: J Pharm Policy Pract. 2019;12:5.